Optimizing the role of youth cadre through education about the impact of drug abuse on adolescents - Isrofah, I.; Prastiwi, Dani; Handoko, Redy (Journal of Community Service and Empowerment, 2021)
Adolescents are a very vulnerable age at risk of drug abuse. Through the empowerment of youth Posyandu (health center) cadres in education about the impact of drug abuse, it is expected to be one of the promotive and preventive efforts so that teenagers are not entangled in drug abuse. This community service program aimed to provide socialization to youth Posyandu cadres about the dangers of drug abuse. This activity was attended by 40 participants who had previously taken the Covid-19 screening test to ensure this activity was safe to do at the Sumurjomblangbogo Village Hall, Pekalongan. Pretest and Posttest were conducted to measure the knowledge of cadres before and after being given education. The results of this community service, can increase the knowledge of cadres from the majority of good knowledge (70%) to very good (90%). Similar activities are needed to develop youth Posyandu cadres to have health maintenance skills. Of course, it takes support and participation from residents and village officials.